Rich lands and poor : the road to world posperity - Myrdal, Gunnar (New York : Harper & Brothers, 1957)
This volume presents the thought and belief of its author and points to the way in which religion, philosophy, art, science, economics, politics and history may constitute that form of human activity which takes the fullest and most precise account of various-ness, possibility, complexity and difficulty.
Volume 16.
Includes bibliographical references.
Loans
osa 24/08/18
Keywords: Economic development; Developing countries